Analisis Pengaruh Potensi Ekonomi Sektor Pariwisata terhadap Pendapatan Asli Daerah (Pad) 5 Provinsi di Pulau Jawa - Hasna, Dhiyaa Fachra Aulia; Barakatuminalloh, Barakatuminalloh (Lingka Ekonomika, 2025)
The tourism sector in Indonesia, particularly on the island of Java, has great potential, but its contribution to local government revenue remains low, leading to a reliance on central government transfers. This study analyses the impact of the number of tourist destinations, per capita GDP, tourist accommodation, and road length in five provinces on the island of Java from 2013 to 2023 using panel data regression with a fixed effects model. The results indicate that, collectively, all four variables significantly influence PAD, while individually, only tourist accommodation and road length have a significant impact. Implications suggest that policies should focus on improving the quality of accommodation services, developing and upgrading road networks, and standardising accommodation facilities.